Paranasal sinus’s osteom: one of reasons for headache? - Skorobogatyy, V. V.; Nikitchin, S. D.; Robeiko, K. G. (Modern medical technology, 2019)
Clinical observation and surgical treatment of osteoma occupying several paranasal sinuses are presented.